Implementasi Akhlakul Karimah Siswa SMK Negeri 2 Bukittinggi Di Lingkungan Sekolah Tahun Ajaran 2021/2022 - Sintania Wendri; Muhiddinur Kamal; Iswantir M; Charles Charles (Al-Tarbiyah : Jurnal Ilmu Pendidikan Islam, 2023)
The importance of education makes someone who lives in society experience growth that is oriented towards safety and the highest happiness in life. "Education is a demand in the life of children's growth, meaning that education is demanding all the natural strengths that exist in children so that they as humans and as members of society can achieve the highest safety and happiness." Apart from making someone achieve safety and high happiness, education will also lead someone to a peaceful life, who has faith and devotion to God Almighty, has noble morals, is skilled, socialist, intelligent and independent. The aim of this research is to determine the implementation of akhlakul karimah students at SMK Negeri 2 Bukittinggi in the school environment and to determine the supporting and inhibiting factors for the implementation of akhlakul karimah for students in Class XII Hospitality at SMK Negeri 2 Bukittinggi. This research is a descriptive qualitative research. The research location was at SMKN 2 Bukittinggi, the research subjects were teachers and students. This research was conducted in June 2022. Data collection techniques were observation, interviews, and documentation. The data validation technique is technical triangulation and time triangulation. Data analysis techniques are data reduction, data presentation, and data verification. The results showed that the Akhlakul karimah students of SMKN 2 Bukittinggi had been implemented at SMKN 2 Bukittinggi. The steps in instilling akhlakul karimah students in the school environment are through habituation, evaluation of school regulations. Supporting factors for akhlakul karimah include the willingness of students, the example of teachers, and the environment. While the inhibiting factor is the lack of environmental student desire, facilities and infrastructure that are less supportive.